Ultra-processed food consumption and quality of life: a cross-sectional study in Iranian women - Hosseininasab, Dorsa; Shiraseb, Farideh; Bahrampour, Niki; da Silva, Alessandra; Hajinasab, Mohammad Mahdi; Bressan, Josefina; Mirzaei, Khadijeh (Frontiers in Public Health, 2024)
Background: Ultra-processed foods (UPFs) has been associated with higher intake of added sugars, sodium, and unhealthy fats, but the associations of UPFs with quality of life (QoL) is not well known. Methods: The present cross-sectional study was conducted on 193 Iranian women aged 18-48 years and body mass index (BMI) ≥ 25 kg/m². UPFs were identified using the NOVA classification. QoL was evaluated using SF -36 questionnaires. Anthropometric measurements and body composition were assessed using an appropriate method. Results: The mean of BMI and fat free mass (FFM) of subjects were 30.90 kg/m2 and 46.69 kg, respectively. At first, a significant difference was found in height of women according to tertiles of UPFs consumption. The mean score of total QoL scale was 66.90. Women who were in the tertile 3 of UPFs intake had 23.59 units lower the scale of limitation in physical capabilities and activity (score of role-physical) (β= -23.59, 95% CI: -37.77–9.40, P= 0.001). Highest adherence to UPFs intake reduced 8.76 units in addressing feelings of energy and fatigue (vitality domain) in model 2 (β= -8.76, 95% CI: -16.42–1.11, P= 0.02). Finally, 15.78 decreasing units were found at mental states of anxiety and depression (mental health scale) between participants of the third tertile of UPFs intake (β= -15.78, 95% CI: -24.11- -7.45, P<0.001). Conclusion: The higher UPF consumption was associated with poorer QoL in Iranian women. Further studies are needed to confirm these data and to identify effective strategies to promote healthy food choices.